Impact of long-term integrated nutrient management on productivity, profitability, soil microbial activity and nutrient content ofrice (Oryza sativa) in Assam - DIDAWAT, RISHBH KUMAR; SHARMA, VINOD KUMAR; NATH, D J; KUMAR, SANDEEP; DEY, ABIR; KUMAR, PRAVEEN; SHANKAR, KRIPA; CHOPRA, INDU; SHIVAY, Y S; PARIHAR, C M; PRASAD, SHIV (The Indian Journal of Agricultural Sciences, 2024)
A study was carried out during 2021 to 2022 at Assam Agricultural University, Jorhat, Assam to study the effect of long-term integrated nutrient management on productivity, profitability, soil microbial activity and nutrient content of rice (Oryza sativa L.) in Assam. The experiment was conducted in a randomized block design (RBD) comprised of 5 nutrient management practices, viz. T1, Absolute control; T2, 100% recommended dose (RD) through chemical fertilizers (CF); T3, 50% RD through CF + liquid biofertilizers; T4, 50% RD through CF + solid biofertilizers; and T5, 50% RD through CF + enriched compost (EC) (@1 t/ha), with 4 replications. The results showed higher grain yield and profitability in treatment T2 (5.23 t/ha and 1472.29/ha) followed by T5 (5.23 t/ha and 1446.29/ha), T3 (4.90 t/ha and 1362.29/ha), T4 (4.87 t/ha and 1346.69/ha), and the lowest in T1 (3.21 t/ha and 897.85/ha). Notably, treatment T5 delivered comparable yield and returns to T2. However, treatment T5 significantly increased the essential nutrients (N, P, K, Zn, Cu, Mn, Fe) in grain compared to T2 or T3/T4. In addition, soil microbial activity such as dehydrogenase activity, phospho-monoesterase activity, microbial biomass carbon, fluorescein diacetate hydrolase, and arylsulphatase activity were significantly higher under treatment T5. These findings highlight that treatment T5 i.e. 50% CF + EC (@1 t/ha) not only matches conventional 100% fertilizer application in yield and returns but also enhances soil microbial activity. Study highlights the potential of integrated nutrient management practices with 50% RD through CF + enriched compost (EC) (@1 t/ha) to address micronutrient deficiencies, improve crop productivity, profitability, and promote sustainable agriculture in the region.